Saving, investment, capital stock and current account projections in long-term scenarios - Guillemette, Yvan (OECD Economics Department Working Papers, 2018)
The paper describes the framework used in long-term economic scenarios for the projection of the saving rate, investment, capital stock and current account. The saving rate is determined according to an estimated equation which suggests that demographics, captured by the old-age dependency rate and life expectancy, is a major driver, with additional effects from the fiscal balance, labour productivity growth, the net oil trade balance, the availability of credit and the level of social protection. The evolution of the business sector capital stock depends on the economy's cyclical position, product market regulation, employment protection legislation and the user cost of capital, and may be constrained by current account deficits depending on the degree of capital account openness. Business sector investment is derived from the capital stock projection via the usual stock-flow identity. The public sector capital stock-to-output ratio is assumed to be constant in the baseline scenario, but a public investment shock can be simulated in alternative scenarios. The current account balance is obtained as the difference between national investment and saving, and in turn determines the evolution of the net international investment position. A global interest rate premium helps to bring global saving and investment into balance